Measuring customer satisfaction - Ellis, Lynn W; Curtis, Carey C (Research-technology Management, 1995)
Survey research on measuring customer satisfaction using an index, market share and a lead user confirms that satisfaction must be with the firm as an innovator well as with the innovative service or product. The customer is defined as not only the end user or consumer but as a downstream counterpart of R&D in the same company or in other parts of the distribution chain. For an overall indication of customer satisfaction, measure the firm's responsiveness, its technology (capabilities and products) and product quality/reliability.
11 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/062-719-370-151-663 tex.type: [object Object]
Keywords: dept.acc